High quality chalcogenide-silica hybrid wedge resonator - Kang, Gumin; Krogstad, Molly R.; Grayson, Michael; Kim, Dae-Gon; Lee, Hansuek; Gopinath, Juliet T.; Park, Wounjhang (OPTICAL SOC AMER, 2017)
Chalcogenide glasses, with high nonlinearity and low loss, have captured research interest as an integrated device platform for near-and mid-infrared nonlinear optical devices. Compared to silicon-based microfabrication technologies, chalcogenide fabrication processes are less mature and a major challenge is obtaining high quality devices. In this paper, we report a hybrid resonator design leveraging a high quality silica resonator to achieve high Q factors with chalcogenide. The device is composed of a thin chalcogenide layer deposited on a silica wedge resonator. The hybrid resonators exhibit loaded Q factors up to 1.5 x 10(5) in the near-infrared region. We also measured the effective thermo-optic coefficient of the device to be 5.5x10(-5)/K, which agreed well with the bulk value. Thermal drift of the device can be significantly reduced by introducing a titanium dioxide cladding layer with a negative thermo-optic coefficient. (C) 2017 Optical Society of America
Keywords: WAVE-GUIDES; INDEX; FILMS